Diné (Navajo) female perspectives on mother-daughter communication and cultural assets around the transition to womanhood: a cross-sectional survey - Jennifer Richards; Rachel Strom Chambers; Jaime Lynn Begay; Kendrea Jackson; Lauren Tingey; Hima Patel; Scott Carvajal; Stephanie Russo Carroll; Nicolette Teufel-Shone; Allison Barlow (BMC, 2021)
Abstract Background The inclusion of protective factors ("assets") are increasingly supported in developing culturally grounded interventions for American Indian (AI) populations. This study sought to explore AI women's cultural assets, perspectives, and teachings to inform the development of a culturally grounded, intergenerational intervention to prevent substance abuse and teenage pregnancy among AI females. Methods Adult self-identified AI women (N = 201) who reside on the Navajo Nation completed a cross-sectional survey between May and October 2018. The 21-question survey explored health communication around the transition to womanhood, cultural assets, perceptions of mother-daughter reproductive health communication, and intervention health topics. Univariate descriptive analyses, chi squared, and fisher's exact tests were conducted. Results Respondents ranged in age from 18 to 82 years, with a mean age of 44 ± 15.5 years. Women self-identified as mothers (95; 48%), aunts (59; 30%), older sisters (55; 28%), grandmothers (37; 19%), and/or all of the aforementioned (50; 25%). 66% (N = 95) of women admired their mother/grandmother most during puberty; 29% (N = 58) of women were 10-11 years old when someone first spoke to them about menarche; and 86% (N=172) felt their culture was a source of strength. 70% (N = 139) would have liked to learn more about reproductive health when they were a teenager; 67% (N = 134) felt Diné mothers are able to provide reproductive health education; 51% (N = 101) reported having a rite of passage event, with younger women desiring an event significantly more than older women. Responses also indicate a disruption of cultural practices due to government assimilation policies, as well as the support of male relatives during puberty. Conclusions Results informed intervention content and delivery, including target age group, expanded caregiver eligibility criteria, lesson delivery structure and format, and protective cultural teachings. Other implications include the development of a complementary fatherhood and/or family-based intervention to prevent Native girls' substance use and teen pregnancy.